Аnalysis of large elastic-plastic deformations elliptic plates for loading quasistatic - Астанін, В.В.; Лепіхін, П.П.; Корбач, В.Г.; Сторожук, В.М. (Proceedings of National Aviation University, 2006)
The accuracy of earlier obtained energy-approach-based analytical relations for sagging prediction of the central point of elliptical plate subjected to hydrostatical indentation has been determined by comparison with the results of numerical calculations and known experiments. The influence of geometry on the sagging of elliptical plates made of elastoplastic strengthening materials has been investigated.